Short Communication: Benthic macroinvertebrate diversity as biomonitoring of organic pollutions of river ecosystems in Central Java, Indonesia - DWI NUGROHO WIBOWO; SETIJANTO SETIJANTO; SLAMET SANTOSO (Society for Indonesian Biodiversity, 2017)
Wibowo DN, Setijanto, Santoso S. 2017. Short Communication: Benthic macroinvertebrate diversity as biomonitoring of organic pollutions of river ecosystems in Central Java, Indonesia. Biodiversitas 18: 671-676. Benthic macroinvertebrates are mainly aquatic insects that spend most of their lives in the freshwater ecosystems. The physical, chemical, and biological conditions of rivers have a direct influence towards aquatic insects (Ephemeroptera, Plecoptera, and Trichoptera EPT) which make them good indicators of stream water quality. We examined the use of benthic macroinvertebrates diversity as a biomonitoring tool to assess organic pollution levels in three rivers in Purwokerto city during March to October 2011. Our objective was to test the sensitivity of benthic macroinvertebrates especially Ephemeroptera, Plecoptera, and Trichoptera (EPT) diversity to organic pollution levels reflected by biological oxygen demand (BOD) concentrations. A total of 27 sites with different BOD levels were surveyed in three different rivers (Logawa, Banjaran, and Pelus) during the period of March to October 2011. The results revealed no correlation of benthic macroinvertebrate diversity (EPT index) to BOD levels. It could be concluded that in the use of EPT index as bioindicators of waters condition, the number of samples, sampling time, and location should be considered.